A cross-tissue transcriptome-wide association study identifies novel susceptibility genes for lung cancer in Chinese populations. Issue 17 (28th April 2021) - Zhu, Meng; Fan, Jingyi; Zhang, Chang; Xu, Jing; Yin, Rong; Zhang, Erbao; Wang, Yuzhuo; Ji, Mengmeng; Sun, Qi; Dai, Juncheng; Jin, Guangfu; Chen, Liang; et al.
Abstract: Although dozens of susceptibility loci have been identified for lung cancer in genome-wide association studies (GWASs), the susceptibility genes and underlying mechanisms remain unclear. In this study, we conducted a cross-tissue transcriptome-wide association study (TWAS) with UTMOST based on summary statistics from 13 327 lung cancer cases and 13 328 controls and the genetic-expression matrix over 44 human tissues in the Genotype-Tissue Expression (GTEx) project. After further evaluating the associations in each tissue, we revealed 6 susceptibility genes in known loci and identified 12 novel ones. Among those, five novel genes, including DCAF16 ( P cross-tissue = 2.57 × 10 −5, P Lung = 2.89 × 10 −5 ), CBL ( P cross-tissue = 5.08 × 10 −7, P Lung = 1.82 × 10 −4 ), ATR ( P cross-tissue = 1.45 × 10 −5, P Lung = 9.68 × 10 −5 ), GYPE ( P cross-tissue = 1.45 × 10 −5, P Lung = 2.17 × 10 −3 ) and PARD3 ( P cross-tissue = 5.79 × 10 −6, P Lung = 4.05 × 10 −3 ), were significantly associated with the risk of lung cancer in both cross-tissue and lung tissue models. Further colocalization analysis indicated that rs7667864 (C > A) and rs2298650 (G > T) drove the GWAS association signals at 4p15.31–32 (OR = 1.09, 95%CI: 1.04–1.12, P GWAS = 5.54 × 10 −5 ) and 11q23.3 (OR = 1.08, 95%CI: 1.04–1.13, P GWAS = 5.55 × 10 −5 ), as well as the expression of DCAF16 (βGTEx = 0.24, P GTEx = 9.81 × 10 −15 ; βNJLCC = 0.29, P NJLCC = 3.84 × 10 −8 ) and CBL (βGTEx = −0.17, P GTEx = 2.82 × 10 −8 ; βNJLCC = −0.32, P NJLCC = 2.61 × 10 −7 ) in lung tissue. Functional annotations and phenotype assays supported the carcinogenic effect of these novel susceptibility genes in lung carcinogenesis.